Assessing the relationship between male alcohol consumption and intimate partner violence against women in Sub-Saharan Africa: A dual-dataset secondary analysis of recent DHS surveys - Tilahun Belete Mossie; Haile Mekonnen Fenta; Meseret Tadesse; Animut Tadele (PLoS ONE, 2026)
Background Even if the effects of alcohol use on Intimate Partner Violence (IPV) are well documented, most of the research were from developed countries. Sub Saharan Africa is famous for higher rates of IPV, yet its relationship with partners alcohol consumption is rarely studied. This project focused on assessing the relationship between partners alcohol consumption and IPV against married women, using dual dataset for men and women. Methods We used the recent 2021–2022 Demographic and Health Survey (DHS) dataset for five countries in Sub Saharan Africa. We accessed the dataset on February 13, 2024. The data was anonymous, and there was no any personal identifier. The dataset included 37,465 participants. We used women questionnaire to determine IPV and related factors, and partner’s questionnaire for alcohol and related factors. STATA 18 was used for analysis. A generalized linear mixed model (GLMM) used to estimate the effect of partner alcohol consumption and other factors on IPV. We determined the level of significance at p-value of less than.05. Result The prevalence of IPV was 33.6% [32.9–34.2%]; and that of partner alcohol consumption accounted 25% [24.5–25.4%]. Partner alcohol consumption increased the odds of physical, emotional, sexual, and any form of IPV. Conclusion Partner alcohol consumption increased the odds of IPV, which suggests that partner inclusive intervention packages might be effective in addressing IPV against women in SSA.